Improving Understanding of Sharia Investment in the PAC Fatayat Metro Utara Community, Metro City - Ambariyani, Ambariyani; Nurhayati, Putri; Fudoli, M. Fahmi; Farida, Annikmah; Khotamin, Nur Alfi; Adzkiyaunuha, Moh.; Vela, Anggita; Badarudin, Badarudin; Ikhwanudin, Ikhwanudin (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
In Indonesia, there are two primary investment forms: conventional and sharia. Many people need help understanding the difference between the two. Sharia investment is an investment that is based on Islamic principles and laws. This study aims to improve the understanding of sharia investment in the PAC Fatayat Metro Utara community in Metro City. Currently, many community members do not understand the concept of sharia investment properly, so they are still vulnerable to investment fraud that is not legally clear and promises large profits in a short time. Awareness of the importance of investment as long-term savings that can provide benefits in the future needs to be increased. This is important so that people are aware of investment offers that have been rampant lately, especially investments that claim to be Sharia-based but are not by Islamic principles. This study found that the PAC Fatayat Metro Utara community's understanding of sharia investment could be more robust. Therefore, more intensive education and socialization are needed so that this community can recognize and choose investments based on Sharia principles and avoid fraudulent investments. By increasing public understanding, especially among the PAC Fatayat Metro Utara community, it is hoped that the number of investment fraud victims under Sharia's guise can be minimized. Proper education will have a long-term positive impact on the economic welfare of society.